2019
DOI: 10.1007/s40314-019-0922-5
|View full text |Cite
|
Sign up to set email alerts
|

On the rate of convergence of spectral collocation methods for nonlinear multi-order fractional initial value problems

Abstract: Multi-order fractional differential equations are motivated by their flexibility to describe complex multi-rate physical processes. This paper is concerned with the convergence behavior of a spectral collocation method when used to approximate solutions of nonlinear multi-order fractional initial value problems. The collocation scheme and its convergence analysis are developed based on the novel spectral collocation method which has been recently presented by Wang et al. (J Sci Comput 76(1):166-188, 2018) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…For b = 3, () becomes the same example investigated in the literature 24,25 . The corresponding Yfalse(xfalse)=6()x+12σ, which is smooth on the interval [− 1,1] for σ.…”
Section: Numerical Experimentsmentioning
confidence: 96%
See 2 more Smart Citations
“…For b = 3, () becomes the same example investigated in the literature 24,25 . The corresponding Yfalse(xfalse)=6()x+12σ, which is smooth on the interval [− 1,1] for σ.…”
Section: Numerical Experimentsmentioning
confidence: 96%
“…, which is smooth on the interval [− 1,1] for ∈ N. From Table 1, we can see the proposed method is applicable and gives high accurate results comparing with the results given in previous studies. 24,25 For b = 2.5, we get Y (x) = 3.75…”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the Galerkin spectral method, various collocation methods have been developed starting from (1) Legendre basis (LCM) [ 100 , 134 ] and (2) Jacobi basis (JCM) [ 105 , 152 ]. Zaky constructed a LCM to solve both linear and nonlinear boundary value problems [ 100 ], and later extended this method to simulate initial value DODEs [ 99 , 153 ]. Results indicated that the convergence error decays exponentially with an increasing number of Gauss–Legendre points.…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…In this paper, we use a non-local representation of the solution of the distributed-order time-fractional Rayleigh-Stokes problem to introduce spectral solutions. The spectral and pseudospectral methods are well-known for their high accuracy and have been used extensively in scientific computation, see [33][34][35][36][37][38][39][40][41] and the references therein. The main contribution of this paper is to develop Jacobi-Galerkin algorithms for solving the multidimensional distributed-order time-fractional Rayleigh-Stokes problem (1).…”
Section: Introductionmentioning
confidence: 99%